Copyright Division in the Concept of Mawaris and Copyright Act No.28 Years 2014 - Elina Adi wijayanti; Wahyudi Bakrie (Journal of Indonesian Comparative of Syari'ah Law, 2019)
AbstractCopyright is the right of Intellectual Property (right over the wealth of Intellectual). The rightover the wealth of intellectual, is the right to enjoy economic result of some intellectual creativity. Inthe terms of copyright in Copyright Act No.28 year 2014 explained that “copyright is an exclusiveright of the creator or the right recipient to announce or reproduce the creation or give permission for itwithout any reduce a limitations or restrictions according to the applicable law”. In this case, copyrightcan be transfer to the inheritor or to the other parties. This research aims to know the division ordinancesin inheritance in the concept of mawaris and copyright Act No.28 years 2014. This transfer is aimsto respect the struggle, thought, creativity of the creator, and to keep the benefts felt by society and hisinheritor. The fnding of study are according to copyright act, the creation that get a copyright is all ofcreation in art and science that metioned in copyright act. In Islam not all of creation get a protectionby copyright but it must to have some of requirements as pure, halal or legal, thayyib or good, and itdoesn’t damage a moral of society. The copyright division in inheritance is regulated in civil law bookand mawaris concept. Takharruj system or mutual agreement system is allowed be use after the divisionin the concept of mawaris.Keyword: Copyright, Mawaris, Intellectual property, Sharia